2021
DOI: 10.3389/fphar.2021.706249
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Profiling Study of Realgar-Induced Acute Kidney Injury in Mice

Abstract: Realgar has been used as a type of mineral drug that contains arsenic for thousands of years. Previous studies have shown that Realgar-induced acute kidney injury is associated with abnormal metabolism, but the underlying mechanism is poorly understood. The aim of this study is to investigate the metabolic changes in serum and kidney tissues of mice exposed to Realgar by using a metabolomic approach and explore the molecular mechanisms of acute kidney injury induced by Realgar. Forty mice were randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Traditional Chinese medicine (TCM), the great treasure of the Chinese nation, plays an important value with its unique advantages ( He et al, 2019 ; Luo et al, 2019 ; Jiang et al, 2020 ; Lin et al, 2020 ; Qiu et al, 2020 ; Wu et al, 2021 ). However, more recently, with the wide application of TCM, adverse reactions (like hepatotoxicity) have been attracted growing attention worldwide ( Xie et al, 2020a ; Liu et al, 2021 ; Zhang S. et al, 2021 ). Therefore, how to reduce the liver toxicity is the key link to ensure the safety of TCM ( Chu et al, 2017 ; Zhou et al, 2018 ; Jin et al, 2019 ; Ruan et al, 2019 ; Deng et al, 2020 ; Zhang W. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM), the great treasure of the Chinese nation, plays an important value with its unique advantages ( He et al, 2019 ; Luo et al, 2019 ; Jiang et al, 2020 ; Lin et al, 2020 ; Qiu et al, 2020 ; Wu et al, 2021 ). However, more recently, with the wide application of TCM, adverse reactions (like hepatotoxicity) have been attracted growing attention worldwide ( Xie et al, 2020a ; Liu et al, 2021 ; Zhang S. et al, 2021 ). Therefore, how to reduce the liver toxicity is the key link to ensure the safety of TCM ( Chu et al, 2017 ; Zhou et al, 2018 ; Jin et al, 2019 ; Ruan et al, 2019 ; Deng et al, 2020 ; Zhang W. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics studies have revealed that oral administration of realgar disrupts endogenous metabolites and related metabolic pathways in mice [ 101 ]. Follow-up kidney proteomic studies have revealed that apoptosis and oxidative stress might be related to realgar-induced nephrotoxicity in mice [ 102 ].…”
Section: Realgarmentioning
confidence: 99%
“…A growing number of studies have confirmed the conversion of soluble arsenic into different valence states of arsenic in organisms with different magnitudes of toxicity (Wu et al, 2020; Yi et al, 2020). We have studied the absorption and distribution of soluble arsenic of Realgar in rats and mice and found that arsenic accumulates more in the kidney and is eventually excreted from the kidney (Yi et al, 2018; Zhang et al, 2021a,b). Although the cause of toxicity of Realgar has been identified, the specific mechanism of Realgar toxicity has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%